2022
DOI: 10.1186/s13071-022-05291-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium infection suppresses colon cancer growth by inhibiting proliferation and promoting apoptosis associated with disrupting mitochondrial biogenesis and mitophagy in mice

Abstract: Background Colon cancer is a common gastrointestinal tumor with a poor prognosis, and thus new therapeutic strategies are urgently needed. The antitumor effect of Plasmodium infection has been reported in some murine models, but it is not clear whether it has an anti-colon cancer effect. In this study, we investigated the anti-colon cancer effect of Plasmodium infection and its related mechanisms using a mouse model of colon cancer. Methods An expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Intraperitoneally injected Plasmodium has been shown to reduce MMP9 production by inhibiting IGF-1 signaling through the accumulation of hemozoin, thus inhibiting tumor angiogenesis in vivo ( Wang et al., 2020 ). In addition, tumor cells from Plasmodium -infected mice exhibited increased expression of Bax, caspase-9, and cleaved caspase-3 proteins, while Bcl-2 expression was decreased, resulting in the promotion of mitochondria-mediated apoptosis ( Yao et al., 2022 ). Unfortunately, the specific pathways regulating these non-immune mechanisms following Plasmodium infection remain unclear, necessitating further molecular studies to elucidate the mechanisms involved.…”
Section: Plasmodiummentioning
confidence: 99%
“…Intraperitoneally injected Plasmodium has been shown to reduce MMP9 production by inhibiting IGF-1 signaling through the accumulation of hemozoin, thus inhibiting tumor angiogenesis in vivo ( Wang et al., 2020 ). In addition, tumor cells from Plasmodium -infected mice exhibited increased expression of Bax, caspase-9, and cleaved caspase-3 proteins, while Bcl-2 expression was decreased, resulting in the promotion of mitochondria-mediated apoptosis ( Yao et al., 2022 ). Unfortunately, the specific pathways regulating these non-immune mechanisms following Plasmodium infection remain unclear, necessitating further molecular studies to elucidate the mechanisms involved.…”
Section: Plasmodiummentioning
confidence: 99%
“…There are numerous studies that have shown that there is a close link between mitochondria and cancer development [ 2 ]. As mitochondria play a key role in cell proliferation and death, many studies have demonstrated that targeting mitochondria can inhibit tumor growth or induce apoptosis [ 3 ]. Targeted chemotherapy involves several approaches, including selective enzyme inhibition, which has been recognized as an attractive strategy for inhibiting tumour growth [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%